2007
DOI: 10.1038/nphys728
|View full text |Cite
|
Sign up to set email alerts
|

Is the outer Solar System chaotic?

Abstract: One-sentence summary: Current observational uncertainty in the positions of the Jovian planets precludes deciding whether or not the outer Solar System is chaotic. 100 word technical summary: The existence of chaos in the system of Jovian planets has been in question for the past 15 years. Various investigators have found Lyapunov times ranging from about 5 millions years upwards to infinity, with no clear reason for the discrepancy. In this paper, we resolve the issue. The position of the outer planets is kno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 25 publications
3
28
0
1
Order By: Relevance
“…The author has reported related results for integrations lasting 10 9 yr (Hayes 2007). The essential conclusion is the same, in that even after 10 9 yr, there remain some ICs (about 10 per cent) that show no evidence of chaos, although some of the ICs appearing as regular over 200 Myr develop exponential divergence later.…”
Section: Resultsmentioning
confidence: 99%
“…The author has reported related results for integrations lasting 10 9 yr (Hayes 2007). The essential conclusion is the same, in that even after 10 9 yr, there remain some ICs (about 10 per cent) that show no evidence of chaos, although some of the ICs appearing as regular over 200 Myr develop exponential divergence later.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of the inner planets are crudely taken into account by adding their masses and momenta to those of the Sun. It has been shown, albeit with a small number of samples, that this system contains some initial conditions within observational uncertainty that show chaos on a Lyapunov time-scale of a few Myr, while other initial conditions also within observational uncertainty show no observable chaos on time-scales ranging from 200 Myr to 5 Gyr (Hayes 2007(Hayes , 2008. The goal of our first experiment is simply to explore more fully the structure of Lyapunov times that exist in this system, with initial conditions that are (mostly) within observational error of their true positions.…”
Section: S T Ru C T U R E O F C H Ao S I N T H E I S O L At E D F I Vmentioning
confidence: 92%
“…The chaos in the inner SS was soon verified by full numerical integration of all the planets, but here chaos was also observed in the outer planets (Sussman & Wisdom 1992). This led to uncertainty about the existence of chaos in the outer SS that was resolved by demonstrating that both chaotic and apparently regular orbits exist within observational uncertainty (Hayes 2007(Hayes , 2008.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Researchers have found that double-double or quad-double arithmetic is required to avoid severe numerical inaccuracies, even if other techniques are employed to reduce numerical error [45]. We also mention the recent studies of W. Hayes [43], where some comparisons of the stability (see Figure 1) of the solar system are performed using various numerical ordinary differential equation (ODE) integrators and checked to higher precision using a Taylor series integrator, performed using 19-digit Intel Extended precision.…”
Section: Planetary Orbit Calculationsmentioning
confidence: 99%